The Sierra de Cachi (Salta, NW Argentina): geological evidence about a Famatinian retro-arc at mid crustal levels - Hongn, F.D.; Tubía, J.M.; Esteban, J.J.; Aranguren, A.; Vegas, N.; Sergeev, S.; Larionov, A.; Basei, M. (Journal of Iberian Geology, 2014)
The Cachi mountain ranges, located in Salta (NW Argentina), form an inlier where Neoproterozoic and Paleozoic materials of the Andes crop out in a plutono-metamorphic dome surrounded by Mesozoic and Cenozoic sedimentary rocks. The pre-Mesozoic rocks record a regional metamorphism of low pressure and high temperature conditions, which reached partial melting conditions and was coeval with the intrusion of sheeted granite and trondhjemite plutons. The metamorphic evolution and the emplacement of the plutons took place in an extensional tectonic setting. New U-Pb zircon dating by TIMS and SHRIMP methods yields similar ages for the migmatization (479.7 ± 3.5 Ma) and the emplacement of granites (472.1 ± 11 Ma), constraining the extensional event to Early Ordovician times. We also report the finding of gabbro boulders, which also yield a similar U-Pb SHRIMP zircon age of 477.5 ± 3.9 Ma. So, we propose that the extensional event recognized in Sierra de Cachi took place in a retro-arc setting linked to the Famatinian subduction along the western border of Gondwana. The shortening produced by younger east-verging folds evidences the superposition of a compressional stress field, probably related with the Ocloyic orogeny (Middle/Late Ordovician-Devonian).